INTEGRATIVLIK TIYKARÍNDA OQÍWSHÍLARDÍŃ OQÍP-BILIW BELSENDILIGIN ASÍRÍWDÍŃ DIDAKTIKALÍQ SISTEMASÍ - Annayeva, M.R. (SCIENCE and SOCIETY, 2023)
This article presents information about the effective teaching process, the concept of an integrative approach to science and its role in improving student performance.